1981
DOI: 10.1002/cyto.990010408
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytometric features and mitotic frequency in human breast carcinoma

Abstract: An evaluation of cytometric features of 142 human breast cancers was performed. Twenty-two cytometric features describing density, structure and shape were correlated with mitotic frequency and labeling index of some of the tumors and with the observed recurrence rate of the tumors within 3 years after removal of the breast. A new cytometric measure was also created by combining the four features most strongly correlated with mitotic frequency of the tumors. It was found that the variance of the nuclear area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…",'~More recently, it has been shown that malignant tumors have abnormal DNA level^.^^.^^ It has also been shown that abnormal DNA distribution is correlated with recurrence risk and mitotic frequency. 20 The degree of aneuploidy seems to be an important variable during the whole follow-up period, expressed either as mitotic frequency or variance of DNA content among tumor cell nuclei. These two variables are closely corDifferentiation of the tumor seems to play its main role during the early follow-up period.…”
Section: Cutoff Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…",'~More recently, it has been shown that malignant tumors have abnormal DNA level^.^^.^^ It has also been shown that abnormal DNA distribution is correlated with recurrence risk and mitotic frequency. 20 The degree of aneuploidy seems to be an important variable during the whole follow-up period, expressed either as mitotic frequency or variance of DNA content among tumor cell nuclei. These two variables are closely corDifferentiation of the tumor seems to play its main role during the early follow-up period.…”
Section: Cutoff Pointmentioning
confidence: 99%
“…We were able to clearly demonstrate that some of these cytometric characteristics are correlated with the mitotic activity in the tumor. 20 Diflerentiation: Some studies have shown that tumor differentiation has a predictive value in the diagnosis of breast can~er.~.~~-*'The degree of differentiation of breast cancer is expressed by the tendency of cancer cells to dissociate when a fine-needle biopsy of the tumor is performed. We have recently described a method of expressing this dissociation in quantitative, morphometric terms, i.e., a quantitative measure of tumor differentiat i~n .~' Essentially, the tumor differentiation in that study was expressed as the average size of clusters in epithelial nuclei after division by the mean nuclear area.…”
Section: Computerized Cytophotometrymentioning
confidence: 99%
“…Of several cytometric variables examined through multiple regression analysis, vari ance of nuclear area was the variable most strongly correlated with the mitotic density in cases of human breast carcinoma [5]. The mitotic index of 20 cases of minute colonic carcinoma experimentally induced in rats was greater in differentiated than in undif ferentiated tumors.…”
Section: Mitotic Counts and Proliferative Rate Indicatorsmentioning
confidence: 96%
“…The number of mitoses seen in tissue sections is an important factor in grading many malignancies, especially for the prognosis of breast, ovarian, and other tumors (1, 20,22,29). Also, mitotic activity is a method to evaluate the rate of proliferation of tumors.…”
mentioning
confidence: 99%